Give Justice to the Weak and the Fatherless; Maintain the Right of the Afflicted: A look into the inception of the foster care system in late 19th, early 20th century Kansas and its predecessors - Black, Molly (Kansas State University, The Chapman Center for Rural Studies, 2017)
This paper explores the forms of child welfare prevalent in both Kansas and the entirety of the United States during the time before the modern foster care system became the prevailing norm.
Molly Black, “Give Justice to the Weak and the Fatherless; Maintain the Right of the Afflicted: A look into the inception of the foster care system in late 19th, early 20th century Kansas and its predecessors,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/251.
Keywords: Children's Aid Society; Kansas Children's Home Society; Keaton-Owen Act; Mariadahl; reform school; almhouse